POPULATION STATUS OF WESTERN HORNED TRAGOPAN (T RAGOPAN MELANOCEPHALUS) IN MACHAIRA NATIONAL PARK, AZAD JAMMU AND KASHMIR, PAKISTAN - S. Shabbir; M. Anwar; T. Mahmood; M. A. Beg (Journal of Animal and Plant Sciences, 2018)
The current population status of T. melanocephalus was determined through employing call count method at three sites and 14 selected vantage points i.e., Machiara (7 vantage points), Behri (3 vantage points) and Serli Sacha ( 4 vantage points) of Machiara National Park, Azad Jammu and Kashmir. The finding of this study showed that relative population 2 2 density index of T. melanocephalus at Machiara was 4.37 birds/ Km at Machiara, 2.14 birds/ Km at Behri and 1.52 2 birds/ Km at Serli Sacha. The estimated number of adult birds in Machiara was 16, at Behri was 6 and at Serli Sacha 10 birds. A total of 32 birds were estimated at three sites. Comparatively larger relative population density index of Western Tragopan at Machiara can be attributed to more suitable habitat containing dense vegetation, less disturbance by humans and their livestock as compared to Behri and Serli Sacha. This study provides a preliminary indication that population of Western Tragopan may be recovering in Machiara National Park as a result of better protection measures. Neelum Valley ( Azad Jammu & Kashmir (AJ&K), 3)
Keywords: Western Tragopan; relative population density index; call counts; Machiara National Park.